Deciphering new mechanisms on T‐cell costimulation by human mast cells. Issue 5 (May 2016) - Frossi, Barbara; Mion, Francesca; Pucillo, Carlo
Abstract : This Commentary discusses an article showing that human mast cells not only express co‐stimulatory molecules of the TNFR and CD28 families, but can also co‐stimulate T cells through a CD28‐independent interaction. Abstract : It is well established that full activation of T cells to recognize a specific antigen requires additional signals. These secondary signals are generated by the interaction of costimulatory molecules expressed on APCs. Classical APCs include DCs, macrophages, Langerhans cells, and B cells. However, in recent years, several haematopoietic and nonhaematopoietic cells have been described to express MHC class II antigens and, in appropriate conditions, costimulatory molecules. In this issue, Suurmond et al. [Eur. J. Immunol. 2016. 46: 1132–1141] show, for the first time, that human mast cells not only express costimulatory molecules of the TNF‐receptor and CD28 families, but can also costimulate T cells through a yet‐to‐be‐defined CD28‐independent interaction.